House-Museum of V. E. Borisov-Musatov - Semenov I. V. (Winter school marathon, 2019)
The article describes the house-museum of the famous Russian artist Viktor Elpidiforovich Borisov-Musatov. Located in Saratov, the house-museum attracts a large number of art-lovers of different ages.
Keywords: Victor Elpidiforovich Borisov-Musatov; the house-museum of the artist; the history of the Saratov school of painting; дом-музей художника; Борисов-Мусатов история саратовской школы живописи